Phytochemical profiling and evaluation of antioxidant, anticancer, antimicrobial and antibiofilm activities of endophytic fungi isolated from Lavandula stricta - Samy Selim; Mohamed H. Moustafa; Mohammed S. Almuhayawi; Hattan S. Gattan; Mohammed H. Alruhaili; Mohanned Talal Alharbi; Soad K. Al Jaouni; Hanan M. Alharbi; Fayza Kouadri; Amer M. Abdelaziz (Scientific Reports)
Abstract The emergence of multidrug-resistant pathogens underscores the urgent need for novel antimicrobial agents. In this study, ten endophytic fungal isolates (Ls1–Ls10) were isolated for the first time from Lavandula stricta and evaluated for their antimicrobial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Klebsiella oxytoca, and Candida albicans. The most potent fungal isolate Ls1 was identified as Sarocladium kiliense using morphological and molecular techniques. Phytochemical analysis indicated that the S. kiliense extract is abundant in bioactive compounds, including phenolics, tannins, flavonoids, and alkaloids. The GC mass analysis proved the presence of 41 active compounds in the S. kiliense. Extract including; Benzene, (1-propylnonyl) (9.87%), Hexadecanoic acid (8.05%), Prostaglandin A1-biotin (6.77%), Docosene (6.69%), Octadecenoic acid (5.55%), and 1-Nonadecene (5.16%). The crude extract of S. kiliense showed outstanding anticancer activity against cancerous Hep-G2 and MCF-7 cell lines with IC50 of 31.7 and 49.8 µg/ml, respectively. This isolate exhibited significant antimicrobial activity, with inhibition zones ranging from 16.1 ± 0.1 mm to 35.5 mm. MICs varied between 62.5 and 250 µg/mL. S. kiliense exhibited antioxidant activity and antibiofilm activities. The S. kiliense extract demonstrated concentration-dependent antibiofilm activity. In conclusion, S. kiliense as a hopeful home of bioactive combinations with potent antimicrobial, antioxidant, anticancer, and antibiofilm activities, offering the potential for combating multidrug-resistant pathogens and therapeutic applications.